Blast and Impact Engineering on Structures and Materials - Castedo, Ricardo; López, Lina M.; Santos, Anastasio P. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aimed to collect and present all breakthrough research on all intentional or unintentional explosions and impact problems. During the last decade, the investigation of these phenomena has been an active area of research in different fields (i.e., civil, defense, mining, aeronautical, naval, etc.), including experimental studies, analytical models, or numerical simulations; and this Special Issue is a faithful reflection of this trend.A total of twenty-six papers (twenty-five research papers and one review paper) in various fields of blast and impact engineering including blast loading issues over structures, beams, walls; penetration and impact; explosives safety and security; blasting effects on rocks and tunnels; are presented in this Special Issue.